Justice Aspects of Financial Service Authorities’s Competence for Bankruptcy and PKPU of Financial Service Institutions Based on Law No. 4 Year 2023 - Suwinto Johan; Ariawan Gunadi (Universitas Medan Area, 2023)
The Law on the Development and Strengthening of the Financial Sector was legalized by President Joko Widodo. The Act is known as Law No. 4 of 2023 often known as the P2SK Law, which stipulates that the Financial Services Authority or Otoritas Jasa Keuangan (OJK) is the only party that has the authority to file for bankruptcy and postpone debt payment obligations for financial service institutions. This research will provide novelty, especially on the definition of justice in the financial services sector, especially related to the interests of consumers and creditors with regulatory authority.This right has eliminated the creditor rights of insolvent financial service institutions. Creditors do not have any rights or legal action against defaulting or insolvent financial institutions. This research aims to examine the authority of OJK over bankruptcy and PKPU of Financial Services Institutions and justice for other creditors dan consumers according to the OJK’S authority. This researchers employed the normative juridical method. This study concluded that the authority of the OJK must be reviewed with consideration of the authority already possessed by the OJK, practical conditions in the business world specifically for financial service institutions, and the position and rights of creditors for loans to financial service institutions. The results of the study also found that the authority of the Financial Services Authority did not reflect the value of justice for consumers and creditors